(untitled) (Filološke studije, 2019)
The article illustrates the delicate relationship between Husserl and Heidegger, primarily through the lens of Eugen Fink’s Sixth Cartesian Meditation, which is a continuation of Husserl’s Cartesian Meditations through Heidegger’s language. This calls for a comparison of Husserl’s subjectivity and Heidegger’s existential analysis. The latter roots Dasein once and for all into time, or better, is brings time into Dasein as its primordial truth. Heidegger’s short treatise The Concept of Time here serves as a condensed introduction into his monumental Being and Time. The primary topi cof the article is thus the understanding of time, which proves to be the first troublesome issue and riddle of transcendental subjectivity.